Efforts To Increase The Learning Outcomes Of Class XI IPS- 4 Students In The National Income Subject Through The Application Of Training Methods At SMAN I Rambah In Academic Year 2021/2022 - Nurjannah Nurjannah (Indonesian Journal of Basic Education, 2023)
The research was conducted in class XI IP S - 4 SMAN 1 Rambah in semester 1/Odd semester of the academic year 2021/ 2022. This research activity was carried out in two cycles, namely cycle I and cycle II. Previously, pre-cycle actions were carried out to find out the implementation of learning that had not used a contextual approach. In the pre-cycle where the teacher still uses conventional learning methods, the average test score is 64.78 and the student completeness results are still 52.78% of the 29 students who take the test, only 15 students complete. Student activity in the pre cycle is still 53.57% with quite active category. In cycle I, the teacher has carried out the training approach learning ( Training Methode ) obtained from student learning outcomes obtained an average score of 71.44% and student learning completeness was still 71.42% of the 29 students who took the test there were 26 students who completed their studies. The student activity in the first cycle has increased from the pre-cycle, namely 66.13 or the active category. Although the activities and student learning outcomes from pre-cycle to cycle I have started to increase, they have not reached the expected indicators. Therefore the action continued to cycle II, where the average student learning outcomes were 77.67 and classical learning completeness reached 89.7 %. Likewise, student activity in cycle II also increased, namely 73.44%. or active category. Thus the learning that takes place in cycle II is considered successful because it has reached the indicators. At the planning stage, learning scenarios are prepared and learning tools are prepared. The learning process is carried out using application Training method ( Training method ). The results of the observations were presented in the discussion. At the observation stage, observations of students' activities were carried out and the final results of learning were tested. Performance indicators in the study were the achievement of individual and classical learning mastery of 92.85% . The results of the study prove that the use of learning methods by application Contextual Training ( Training Methode ) can increase the activity and student learning outcomes on National Income materia